Pelatihan Penggunaan Aplikasi Online Pajak Untuk Pembayaran PPh Final Pada Usaha Mikro Siengkong TapiOK - Siska, Elmira; Lestari, Nurlaela Eva Puji; Rachmah, Siti Mabrur; Elvira, Lela (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
This community service activity (PKM) was carried out with a partner, the manager of Siengkong TapiOK, which is one of the MSME actors in the city of Bogor. The problem faced by partners is apart from worrying about eroding profits when paying taxes, there is also limited knowledge in making tax payments online using the OnlinePajak application. This community service activity aims to increase the knowledge and skills of Siengkong TapiOK managers in paying taxes online. Implementation of PKM activities consists of three stages, namely the preparation, implementation and evaluation stages. Recapitulation analysis shows that the material presented is in accordance with partner needs. The statistical results of the paired sample t-test show that this training has proven to have a positive and significant impact on increasing the knowledge and skills of Siengkong TapiOK managers